2018
DOI: 10.1016/j.thromres.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of risk prediction scores for venous thromboembolism following joint replacement

Abstract: Few VTE risk prediction scores in lower limb joint replacement exist and these have methodological issues, have been inadequately reported, not been sufficiently validated, and their impact on patient outcomes and decision making is unknown. Research is urgently warranted in the field. Systematic review registration: PROSPERO 2018: CRD42018088712.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
0
19
1
Order By: Relevance
“…This would allow for potential risk modification by adjusting thromboprophylaxis dosages or using additional antithrombotic medications known to affect TEG parameters. 24,25 Increased age and body mass index and female sex, which are factors known to be associated with increased risk for VTE, 26,27 were not found to be associated with hypercoagulable TEG values in our cohort at 2 and 6 weeks. This was likely due to the small sample size.…”
Section: Discussionmentioning
confidence: 54%
“…This would allow for potential risk modification by adjusting thromboprophylaxis dosages or using additional antithrombotic medications known to affect TEG parameters. 24,25 Increased age and body mass index and female sex, which are factors known to be associated with increased risk for VTE, 26,27 were not found to be associated with hypercoagulable TEG values in our cohort at 2 and 6 weeks. This was likely due to the small sample size.…”
Section: Discussionmentioning
confidence: 54%
“…This may be because they are either very extensive (ie, up to 26 predictors), lack performance, are impractical (ie, include blood measurements), or not properly validated (Table S1). 20 Moreover, unfortunately, none report any performance measures and therefore do not give objective information for potential users. Furthermore, important predictors such as start of mobilization or length of hospital stay are often missing.…”
Section: Current Predictive Models For Vte Following Tha or Tkamentioning
confidence: 99%
“…2 infections were reported in patients with RA, 1 of which responded to antibiotics immediately following surgery and the other required revision 5.3 years following the initial procedure. Patients with RA have an increased risk of prosthetic joint infection following surgery (29,30). Kunutsor et al (30) found an increased relative risk of 1.68 (95% confidence interval [CI], 1.26-2.25) for patients who have taken steroids previously compared to patients who had never taken steroids.…”
Section: Discussionmentioning
confidence: 99%